2022
DOI: 10.18768/ijaedu.1068306
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Benefits and Challenges of Using Blackboard Collaborate as a Remote Learning Tool Among Qassim University Efl Intensive Course Program Students During Covid-19 Pandemic

Abstract: Due to the outbreak of COVID-19 pandemic, using Blackboard platform as a learning tool has dramatically increased in Saudi universities. Still, learners lack effective knowledge of using Blackboard platform. Accordingly, there is a pressing need to concentrate on using Blackboard platform during the COVID-19 pandemic to improve learning outcomes. Therefore, this study was conducted to explore the benefits and challenges of using Blackboard Collaborate as a learning tool by EFL ICP students during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Inadequate technical support and insufficient technical skills were also identified as significant obstacles for teachers and students integrating LMS into their lessons. The studies by Bhalalusesa et al (2013), Suzanne et al (2019), Al-Handhali et al (2020), and Elsayed (2022 also highlight technical problems as commonly faced challenges in LMS usage. In addition to technical issues, teachers and students expressed concerns about the effectiveness of teaching and learning activities on LMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate technical support and insufficient technical skills were also identified as significant obstacles for teachers and students integrating LMS into their lessons. The studies by Bhalalusesa et al (2013), Suzanne et al (2019), Al-Handhali et al (2020), and Elsayed (2022 also highlight technical problems as commonly faced challenges in LMS usage. In addition to technical issues, teachers and students expressed concerns about the effectiveness of teaching and learning activities on LMS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study also showed that lecturers encountered many obstacles in terms of learning style and culture, elearning pedagogy, technological problems, and time management when LMS is integrated into their teaching practice. Meanwhile, Elsayed (2022) conducted a qualitative study to explore the benefits and challenges of using Blackboard Collaborate as a learning tool from the perspectives of EFL students during the COVID-19 pandemic in Saudi Arabia. The data were collected from focus group interviews with 15 students.…”
Section: Previous Studiesmentioning
confidence: 99%
“…LMSs can be used by students to access various educational resources offered by teachers and meanwhile, interact with classmates (Homavazir;Gopal, 2018). In Najran university, Blackboard LMS has been adopted as a platform to manage the educational resources and facilitate synchronous and asynchronous interaction in all courses (Elsayed, 2022). For example, as recommended in a few past studies (Song et al, 2017;Granić;Marangunić, 2019;Byrd, 2014), it offered course content, a synchronous chat room, an asynchronous forum, blogs, online tests, grade displays, notifications, alerts, calendars, and various multimedia files, like images, music, sound, animations, and video clip.…”
Section: Effects Of Bigmentioning
confidence: 99%